Dumb-bell neurinoma of the hypoglossal nerve - Bartal, A. D. (1973)
A unique case of dumb-bell neurinoma of the hypoglossal nerve is presented. The importance of hemiatrophy of the tongue is stressed for early diagnosis of the lesion. The myelocisternogram is the single most important contrast study confirming the intracranial extension of the tumour. Total dissection of the tumour capsule may not be feasible in all cases.